Hyperinsulinemia Down-Regulates TLR4 Expression in the Mammalian Heart - de Laat, Melody A.; Gruntmeir, Kaylynn J.; Pollitt, Christopher C.; McGowan, Catherine M.; Sillence, Martin N.; Lacombe, Véronique A. (Frontiers in Endocrinology, 2014)
Toll-like receptors (TLR) are key regulators of innate immune and inflammatory responses and their activation is linked to impaired glucose metabolism during metabolic disease. Determination of whether TLR4 signalling can be activated in the heart by insulin may shed light on the pathogenesis of diabetic cardiomyopathy, a process that is often complicated by obesity and insulin resistance. The aim of the current study was to determine if supraphysiological insulin concentrations alter the expression of TLR4, markers of TLR4 signalling and glucose transporters (GLUTs) in the heart. First, the effect of insulin on TLR4 protein expression was investigated in vitro in isolated rat cardiac myocytes. Secondly, protein expression of TLR4, the pro-inflammatory cytokines IL-6 and TNF-α, suppressor of cytokine signalling 3 and GLUTs (1, 4, 8, 12) were examined in the equine ventricular myocardium following a prolonged, euglycaemic hyperinsulinaemic clamp. Down-regulation of TLR4 in plasma membrane-rich fractions of rat cardiac myocytes was observed after incubation with a supraphysiologic concentration of insulin as well as in the equine myocardium after prolonged insulin infusion. Further, cardiac TLR4 expression was negatively correlated with serum insulin concentration. Markers of cardiac TLR4 signalling and GLUT expression were not affected by hyperinsulinaemia and concomitant TLR4 down-regulation. Since TLRs are major determinants of the inflammatory response, our findings suggest that insulin infusion exerts an anti-inflammatory effect in the hearts of non-obese individuals. Understanding the regulation of cardiac TLR4 signalling during metabolic dysfunction will facilitate improved management of cardiac sequelae to metabolic syndrome and diabetes.